2003
DOI: 10.1021/jf030151w
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Zinc Absorption from Two Bean (Phaseolus vulgaris L.) Genotypes in Young Women

Abstract: Extrinsic and intrinsic iron and zinc labels were used to test iron and zinc absorption from two bean (Phaseolus vulgaris) genotypes, containing normal (common beans, CB) or higher (HFeZnB) iron and zinc concentrations, fed in single meals to young women with low iron reserves. The women were divided into two groups, with one receiving a CB test meal (n = 12) and the other, an HFeZnB test meal (n = 11). The beans were intrinsically labeled hydroponically with (55)Fe (CB and HFeZnB) and with (70)Zn (HFeZnB). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 39 publications
4
46
1
Order By: Relevance
“…Among HTC grains, TPC was negatively correlated to Zn. Earlier, it has been reported that Fe and Zn bio-availability was negatively affected by the presence of PCs in Phaseolus v. (Donangelo et al 2003). Bean grains were considered to be the best inexpensive source of minerals but their bioavailability was reported to constrain by the presence of anti-nutritional constituents like phytic acid and PCs (Nyombaire et al 2007).…”
Section: Mineral Compositionmentioning
confidence: 99%
“…Among HTC grains, TPC was negatively correlated to Zn. Earlier, it has been reported that Fe and Zn bio-availability was negatively affected by the presence of PCs in Phaseolus v. (Donangelo et al 2003). Bean grains were considered to be the best inexpensive source of minerals but their bioavailability was reported to constrain by the presence of anti-nutritional constituents like phytic acid and PCs (Nyombaire et al 2007).…”
Section: Mineral Compositionmentioning
confidence: 99%
“…In the studies on iron biofortified crops the biochemical tests that were done to test improvement in the iron status were: Inflammation (measured by C-reactive protein and α-1-acid glycoprotein concentrations) [14,15], total body iron [13][14][15][16][17][18]21,22], haemoglobin concentration [16], serum ferritin concentration [13][14][15][16][17], acute phase proteins [18] and serum transferrin receptor concentration [19]. The baseline cut-offs for each of the parameter differed among the studies (Table 2).…”
Section: Methods Of Nutrient Analysesmentioning
confidence: 99%
“…The biofortified crops that were used in the studies were; Vitamin A (Orange) maize [25,26,29], vitamin A (yellow) cassava [24], Vitamin A (Orange) sweet potatoes [23,27,28], high iron beans [13,15,16,19,22], iron pearl millet [14,18,21], Zinc wheat [32], High iron rice [17], high zinc maize [31], High zinc millet [21] and high zinc beans [22].…”
Section: Biofortified Staple Cropsmentioning
confidence: 99%
See 2 more Smart Citations